Tailoring magnetic exchange coupling in Zr2Co11/FeCo nanocomposites via dual-source inert gas condensation: a one-step synthesis approach - Yin Yao; Yan Sun; Jianzhe Sun; Jianhui Bai (Materials Research Express)
This study investigated the synthesis and magnetic properties of Zr _2 Co _11 /FeCo nanocomposites via a one-step dual-source inert gas condensation method. The composite particles were prepared with varying FeCo mass percentages (5%, 10%, and 15%), and their structural and magnetic characteristics were examined. X-ray diffraction confirmed the successful integration of FeCo into the Zr _2 Co _11 matrix. Magnetic measurements revealed enhanced saturation magnetization and effective exchange coupling in Zr _2 Co _11 /FeCo-1 and Zr _2 Co _11 /FeCo-2. However, excessive FeCo in Zr _2 Co _11 /FeCo-3 resulted in less efficient coupling, as indicated by kinks in the hysteresis loop and negative regions in the Henkel plot. These findings underscore the importance of optimizing FeCo content to achieve superior magnetic properties, offering potential for advanced magnetic materials.